Reliability of focal identification of motor fascicles of the ulnar nerve proximal to the wrist: an anatomical study. (March 2020) - Barrett, Justin E.; Farooq, Hassan; Merrell, Gregory A.
We investigated whether motor fascicles of the ulnar nerve can be reliably identified proximal to the wrist. In 17 cadaveric upper limbs, the anterior interosseous nerve was transected at its arborization in the pronator quadratus and transposed to the palmar aspect of the ulnar nerve. The motor fascicular bundle was identified at this level after distinguishing the intraneural epineural involution by microsurgical probing. The motor branch was identified in Guyon's canal and traced retrograde via intraneural dissection to assess accuracy of the original identification. The motor fascicular bundle was found to have been correctly identified in all specimens. We conclude that local anatomic landmarks allow for the motor fascicular group to be correctly identified. Therefore, retrograde, internal dissection of the ulnar nerve is not likely to be required for reliable transfer of anterior interosseous nerve to ulnar nerve motor fascicles.